The influence of facial expressions on attack recognition and response behaviour in karate kumite - Petri, K.; Bandow, N.; Salb, S.; Witte, K. (European Journal of Sport Science, 2019)
Facial expressions play a crucial role in human daily life interactions, so it is possible that they contain relevant anticipatory cues. Therefore, we conducted two studies in karate kumite to analyse the influence of facial expressions on the attack recognition (study A) and on the response behaviour (study B). In study A, 10 karate athletes (age 14-26 years, national and international level) had to recognize temporally occluded karate attacks in 2 conditions (normal and blurred face of the attacker) and identify the upcoming attack (verbal reports). In study B, a natural fight was initiated with 12 karate athletes (age 15-32 years, national and international level) in 3 conditions: an attacker with a normal face, wearing a ski mask, and wearing a ski mask together with sunglasses. The measured parameters response quality and time for response were calculated applying the McNemar test (study A) and Friedman test (study B). Results of study A showed a significant improvement in the attack recognition in the blurred face condition compared to the normal face condition. In study B a significant improvement in time for response was observed in the ski mask and ski mask plus sunglasses conditions (r < 0.1). No significant difference for response quality was found in any of the three conditions. The results of our work indicate that the disguise of the attacker`s face leads to a better attack recognition and response behaviour. We conclude that anticipatory cues in karate kumite context mainly lie in the attacker`s movements and not in the attacker`s face.